1998
DOI: 10.1021/bp9800790
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Activity of Chymotrypsin Using AOT-DOLPA Mixed Reversed Micellar Systems

Abstract: Novel reversed micellar solutions formulated with a mixture of AOT (dioctyl sulfosuccinate) and DOLPA (dioleyl phosphoric acid) show good potential for use in reversed micellar protein extraction operations. Chymotrypsin is easily extracted from an aqueous phase into organic isooctane containing 10 mM AOT and DOLPA in a 4:1 ratio. The extraction ability of the mixed reversed micelles of 10 mM was higher than that of 200 mM AOT alone. The results of extraction indicated that the AOT-DOLPA mixed reversed micelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
4
33
0
Order By: Relevance
“…This raises the question of whether the pH can be manipulated to get better penicillin G extraction at low AOT concentration in an industrial application (it should be noted that penicillin broths are compositionally more complex than those used in this work, which will change the equilibria that can established in the extraction process). The use of a low surfactant concentration would be helpful because amphiphilic molecules are difficult to remove in subsequent downstream processing [18].…”
Section: Partitioning Of Penicillin G Between the Organic And Aqueousmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether the pH can be manipulated to get better penicillin G extraction at low AOT concentration in an industrial application (it should be noted that penicillin broths are compositionally more complex than those used in this work, which will change the equilibria that can established in the extraction process). The use of a low surfactant concentration would be helpful because amphiphilic molecules are difficult to remove in subsequent downstream processing [18].…”
Section: Partitioning Of Penicillin G Between the Organic And Aqueousmentioning
confidence: 99%
“…The polar heads of the surfactant molecules are directed towards the interior of a water-containing sphere, whereas the aliphatic tails are oriented toward the non-polar organic phase. Many authors have investigated the partitioning of proteins between two immiscible liquids, and the considerable success of protein partitioning has provided the motivation for using the technique for antibiotics; in our case penicillin G. Reverse micelles have the ability to extract a variety of biomolecules such as proteins [10,11,[15][16][17][18][19] and enzymes [16,19] into nanometre-size water pools surrounded by a monolayer of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Back-extraction is usually very slow and CaCl 2 is added into the aqueous phase to assist the process (Hu and Gulari, 1996). The limitations of using reverse micelles in the backextraction are due to: (a) the difficulty in separating proteins from the AOT reverse micellar phase and (b) the excessive time involved in the process (Hu and Gulari, 1996;Goto et al, 1998).…”
Section: Reverse Micelles Methodmentioning
confidence: 99%
“…This can be added to AOT to form AOT-DOLPA for use in chymotrypsin extract. Goto et al (1998) reported that the effectiveness of mixed reverse micelles increased with increasing amount of DOLPA added. He also found that 4:1 ratio of AOT: DOLPA was the best for chymotrypsin extraction and that 10 mM of mixed reverse micelles had higher extraction ability than 200 mM of AOT.…”
Section: Reverse Micelles Methodmentioning
confidence: 99%
“…The reverse micelle extraction of proteins is useful for the separation and purification of proteins, 6 enzymatic reactions in organic solvents, 7,8 refolding of denatured proteins, 9,10 etc. To understand the extraction mechanism, many efforts have been made to study the effects of various experimental conditions, which include the natures and concentrations of proteins, surfactants, and aqueous electrolytes and the pH of the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%